Characterisation of diesel injector deposits using advanced analytical techniques - Angel-Smith, Sarah Jane (2018)
Internal diesel injector deposits (IDIDs) have become a prolific issue in the last decade, increased number of incidences have occurred since the introduction of ultra-low sulfur diesel and biodiesel. The IDIDs have caused concerns for customers such as injector systems misfiring or blocking, increased emissions and fuel consumption. Interest into the origins of the deposits has steadily grown, with identified possible causes including contaminants, degraded additives, or thermal and pressure stresses of the engine. Most examples in previous studies only provide surface analysis of IDIDs, however, the surface only provides a relatively small part of the story. In order to understand how an IDID has formed the history needs to be explained, to do this the lower layers of the IDID need to be analysed. Outcomes of this research include the first example of focused ion beam and secondary ion mass spectrometry being used in combination to analyse IDIDs and clearly shows different chemical layers, demonstrating that these deposits are made up of multiple complex chemistries. Raman spectroscopy can provide graphitic content information for IDIDs giving evidence of formation however, a method to remove fluorescence from carbonaceous structures was first devised and validated in order to allow this to be performed. The jet fuel thermal oxidation test (JFTOT) has been proven to be an effective method of replicating deposits on comparison with IDIDs from failed field engines, and key chemistries have been identified for B20 biodiesel and ultra-low sulfur diesel (ULSD). This work has used existing analytical methods to understand IDIDs and found novel insights that have not been previously observed in the literature.